PENINGKATAN KETERAMPILAN PRIMIGRAVIDA DALAM MERAWAT BAYI DENGAN PENERAPAN KOMBINASI METODE BUZZ GROUP DAN MODELLING - Lestaluhu, Viqy; Indrawan, I Wayan Agung; Andarini, Sri (Journal Nursing Care and Biomolecular, 2018)
Introduction: First pregnancy is a critical period for mother life. Primigravida needs sufficient information on baby delivery preparation and baby care skill. This study aims at know the effect of combination buzz group and modelling methods on primigravida skill in taking care of baby. Method: Research design is true experiment using randomized subject, pre-test and post-test control group design. It was conducted at community health care of Poka Rumah Tiga Ambon. The samples of 24 respondents divided into two groups namely experimental and control group. Checklist containing items on bathing the baby, putting on diapers, umbilical cord care and technique of breastfeeding, are used to assess primigravida skill. The data obtained are then analysed using Paired t-test and Mann-Whitney U Test with α=0,05. Result and analysis : The finding shows that there is a significant difference in terms of primigravida skill from thosein before and after the use of combination method of buzz group and modelling (p=0,000). The average score difference was 46,271 (SD=3,758). In addition there was a significant difference between the experimental and control group (p=0,000). Discussion: The method involving pregnant mother in the form of buzz group and modelling an appropriate option for health practitioner in improving the health of mother and baby.